Non-Destructive, Specular Laser Reflectometry and X-Ray Fluorescence Analysis Applied to Coins of the Gallic Roman Empire - Yannic Toschke; Steffen Wolke-Hanenkamp; Eugen Wolf; Achim Lichtenberger; Katharina Martin; H.-Helge Nieswandt; Mirco Imlau (Heritage, 2025)
Non-destructive, specular laser reflectometry, an industrially used and easily accessible method, is adapted in numismatic research to the inspection of coins of the Gallic Roman Empire with the objective of the allocation of mints and/or the identification of different minting techniques. For this purpose, the laser-reflectometric fingerprints of three series of coins each consisting of five antoniniani (or radiates) of the Gallic Roman Empire originating from two mints—Trier and Cologne—are systematically determined, analyzed and correlated with the corresponding XRF element analysis. The results show that the use of an inexpensive red-emitting laser system (wavelength 632.8 nm) with a beam diameter <semantics>d<0.5</semantics> mm and a sample mount that can be adapted to the individual shape and thickness of the coins leads to signal intensities that can be systematically recorded over a large angular range with a very good signal-to-noise ratio (SNR <semantics>>10</semantics>). While the signals cannot be used to assign individual coins to mints, we discuss the possibility of a statistical analysis. Although each coin set consists of only five samples and thus requires further study, the results here suggest that the sets can be distinguished from each other, that there is a correlation to the silver concentration and that it is possible to estimate the refractive index n.